The Effect of a Mind Mapping-Assisted Problem-Based Learning Model on Students' Motivation and Learning Comfort in the Harmony in Ecosystem Material for Fifth-Grade Elementary School Students - Putu Nanda Prastika Priandana Priandana; I Nyoman Jampel Jampel; Kadek Yudiana Yudiana (Universitas Pendidikan Ganesha, 2025)
This study addresses the issue of traditional teaching methods that tend to be one-way and aims to analyze the effect of the Problem-Based Learning (PBL) model assisted by Mind Mapping on students’ motivation and learning comfort in the topic Harmony in Ecosystems for fifth-grade elementary school students. The research population consisted of 137 students. The results of the study show: (1) There is a significant difference in learning motivation between students who received instruction using the PBL model assisted by mind mapping and those who experienced conventional learning methods, as indicated by a tvalue greater than the ttable value (13.728 > 1.67065) and a significance value of 0.000 < 0.05. (2) There is a significant difference in learning comfort, with a tvalue of 11.470 > 1.67065 and a significance value of 0.000 < 0.05. (3) There is a simultaneous significant difference in both motivation and learning comfort, indicated by an Fvalue of 123.718 > Ftable value of 3.153 and a significance level of 0.000 < 0.05. Thus, the PBL model assisted by mind mapping is proven to be more effective in enhancing students' motivation and learning comfort compared to conventional methods.